Prevalence of enamel defects in children attended at a pediatric dental clinic (Research, Society and Development, 2020)
The objective of this article was to evaluate the prevalence of enamel development defects (EDD) in children attended in the discipline of Children's Clinic II of the Dentistry course of the Universidade Federal de Campina Grande (UFCG), in Patos, Paraíba, Brazil. This study was cross-sectional, observational and retrospective using clinical records, from which information was learned about the type of EDD, number of teeth affected, clinical complaint and demographic variables. The data obtained were analyzed with of IBM SPSS Statistics software, worked by descriptive statistics and submitted to fisher's Chi-square and Exact statistical test considered significant at the level of 5% (p